2006
DOI: 10.1016/j.ijid.2004.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcosis in human immunodeficiency virus-negative patients

Abstract: Cryptococcosis is not rare in HIV-negative patients. The mortality rate is high. Early recognition of cryptococcosis and use of appropriate antifungal therapy in these patients may improve clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
106
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 18 publications
12
106
2
3
Order By: Relevance
“…Underlying immunosuppression associated with cryptococcosis in HIV-negative patients has been reported. Hematologic malignancies, autoimmune diseases, sarcoidosis and other diseases that present some degree of immunodefi ciency may be risk factors for cryptococcosis 25 . In our study, four cases of leprosy were associated with cryptococcosis, and we also observed two tuberculosis cases in HIV-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying immunosuppression associated with cryptococcosis in HIV-negative patients has been reported. Hematologic malignancies, autoimmune diseases, sarcoidosis and other diseases that present some degree of immunodefi ciency may be risk factors for cryptococcosis 25 . In our study, four cases of leprosy were associated with cryptococcosis, and we also observed two tuberculosis cases in HIV-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…in HIV/AIDS patients is associated with high mortality [2]. Patients who are given long-term treatment with immunosuppressants, recipients of organ transplantation, those with malignancies, diabetes mellitus, and chronic pulmonary diseases are also susceptible to Cryptococcus infection [3]. In recent years, with the widespread use of broad-spectrum antibiotics, immunosuppressants, glucocorticoids, and chemotherapeutics, and with advances in the diagnosis and treatment of diseases, the incidence of pulmonary cryptococcosis (PC) has increased [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Given that meningitis is the most common presenting illness in patients with cryptococcosis, LP is essential even in the absence of neurological symptoms. 6,7 Untreated cryptococcal meningitis carries a high mortality rate and can lead to cranial nerve palsies, hearing loss, and blindness. 8 According to the current Infectious Diseases Society of America guidelines, non-HIV patients with disseminated cryptococcosis should be treated with a four-week course of amphotericin B and flucytosine for induction therapy followed by maintenance therapy with fluconazole for 6-12 months.…”
Section: Discussionmentioning
confidence: 99%